EVALUASI PERLAKUAN PERSEDIAAN BARANG DAGANGAN PADA PT. PERTANI (PERSERO) CABANG SULAWESI UTARA - Gerungan, Dei Gustiani; Pangemanan, Sifrid S.; Pusung, Rudy J. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
PT. Pertani (Persero) Branch of North Sulawesi is a trading company operating in agriculture sector. Inventory has an important role to maintain the company’s operational stability and determine the company’s level of profit. The main problem in accounting of inventory the inconsistency with PSAK no.14.The purpose of this study is to analysis the consistency between the disclosure of inventory with PSAK no.14. Data was collected by interview, documentation, and initial observation prior research. This study is a qualitative descriptive research. Result show that the company has mostly closure its inventories in accordance with PSAK no.14.Keywords: inventory accounting, psak no.14